Prehospital shock index predicts outcomes after prolonged transport: A multicenter rural study - Bardes, James M; Price, Bradley S; Bailey, Hannah; Quinn, Alexander; Warriner, Zachary D; Bernard, Andrew C; LaRiccia, Aimee; Spalding, M Chance; Linskey Dougherty, Melissa B; Armen, Scott B; Wilson, Alison (The journal of trauma and acute care surgery, 2023)
Shock index (SI) predicts outcomes after trauma. Prior single-center work demonstrated that emergency medical services (EMSs) initial SI was the most accurate predictor of hospital outcomes in a rural environment. This study aimed to evaluate the predictive ability of SI in multiple rural trauma systems with prolonged transport times to a definitive care facility. This retrospective review was performed at four American College of Surgeons-verified level 1 trauma centers with large rural catchment basins. Adult trauma patients who were transferred and arrived >60 minutes from scene during 2018 were included. Patients who sustained blunt chest or abdominal trauma were analyzed. Subjects with missing data or severe head trauma (Abbreviated Injury Scale score, >2) were excluded. Poisson and binomial logistic regression were used to study the effect of SI and delta shock index (∆SI) on outcomes. After applying the criteria, 789 patients were considered for analysis (502 scene patients and 287 transfers). The mean Injury Severity Score was 8 (interquartile range, 6) for scene and 8.9 (interquartile range, 5) for transfers. Initial EMSs SI was a significant predictor of the need for blood transfusion and intensive care unit care in both scene and transferred patients. An increase in ∆SI was predictive of the need for operative intervention ( p < 0.05). There were increased odds for mortality for every 0.1 change in EMSs SI; those changes were not deemed significant among both scene and transfer patients ( p < 0.1). Providers must maintain a high level of clinical suspicion for patients who had an initially elevated SI. Emergency medical services SI is a significant predictor for use of blood and intensive care unit care, as well as mortality for scene patients. This highlights the importance of SI and ∆SI in rural trauma care. Prognostic and Epidemiological; Level IV.